The Genesis of Judaism - Adler, Yonatan (The Biblical archaeology review, 2022)
Throughout much of history, Jewish life and culture have been characterized by strict adherence to the practices and prohibitions given in the Torah. The origins of that observance, however, have remained a mystery. Consider the archaeological discoveries and ancient texts that reveal when and why ordinary Judeans first adopted the Torah as their authoritative law.